Rheography: Harmonic perspectives - S. V. Revenko (Нервно-мышечные болезни)
The review briefly describes the main ways of rheography development. Particular emphasis is laid on the practically forgotten and newly revived method of the harmonic analysis of rheograms. The development of electronics and computed methods of data processing could unveil the potential of this direction of rheography and consider prospects for developing new diagnostic approaches on the basis of a multicyclic harmonic analysis of bioimpedance.